2013
DOI: 10.1007/s13592-013-0240-7
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality of honey bee drones maintained from emergence to sexual maturity under laboratory, semi-field and field conditions

Abstract: International audienceIn order to evaluate the semen quality among honey bee populations, emergent honey bee drones were maintained to sexual maturity for 20 days under laboratory, semi-field, and field conditions. The drones were successfully maintained in laboratory conditions. Drones under laboratory and field conditions presented a lower spermatozoa concentration and lower protein content than those under semi-field conditions. The viability of spermatozoa was higher under laboratory conditions, and the AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 31 publications
2
41
3
Order By: Relevance
“…Indeed, weather conditions, such as precipitation and extreme temperatures, are additional stress factors that can lead to colony weakening [37]. Given that environmental factors and food have a substantial influence on drone maintenance [38,39] and fertility [40][41][42], it is not surprising that the 2 different approaches used in the present study produced slightly different results, similar to what was observed in a previous study [29]. These differences revealed that better survival and maturity rates were achieved when the laboratory method was used (Table 1).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, weather conditions, such as precipitation and extreme temperatures, are additional stress factors that can lead to colony weakening [37]. Given that environmental factors and food have a substantial influence on drone maintenance [38,39] and fertility [40][41][42], it is not surprising that the 2 different approaches used in the present study produced slightly different results, similar to what was observed in a previous study [29]. These differences revealed that better survival and maturity rates were achieved when the laboratory method was used (Table 1).…”
supporting
confidence: 84%
“…The drones and workers used were collected from 15 healthy colonies and homogenized before they were introduced to hives and large cages (Figure A and B). In both approaches, the workers were used to take care of the drones from emergence to sexual maturity (20 d old; Figure C), and the bees were fed with a sugar solution, crushed pollen, and water . Under each rearing condition, the exposed bees were fed steadily with a sugar solution contaminated with fipronil at a low environmental concentration (0.1 μg L −1 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Testing the sperm quality of drones is important to understand the mechanism of biology of honeybee mating, including drone fitness, polyandry, and sperm competition (Ben Abdelkader et al 2014). The usefulness of single tests is very limited for the evaluation of sperm quality in drones (Wegener et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rearing conditions (field, semi-field, laboratory), exposure of brood and adult drones to extreme temperatures, as well as drone age can affect seminal volume and sperm viability [62][63][64][65]. Rearing conditions can affect the number of spermatozoa and seminal proteins as well as ATP (adenosine triphosphate; main energy source for sperm motility) content and SOD (superoxide dismutase; an enzyme that protects cells from oxidative damage) activity [64]. Interestingly, while an immune challenge decreased sperm viability, pollen deprivation in adult drones had no effect [65].…”
Section: Mating Success Health and Quality Of Reproductive Castesmentioning
confidence: 99%